Postoperative Weight Loss Masks Metabolic Impacts of Periodontitis in Obese Rodents. Issue 6 (1st June 2017) - Yu, Ting; Zhao, Li; Huang, Xin; Xie, Meilian; Wang, Xiangli; Ma, Chanjuan; Xu, Yixin; Wang, Yixiong; Xie, Baoyi; Luo, Gang; Zhang, Jincai; Xuan, Dongying
Abstract : Background: Postoperative weight loss (POWL) is expected to occur in combined models of obesity and periodontitis. This study explores the confounding effects of POWL on the impact of ligation‐induced periodontitis on glucose and lipid metabolism in obese animals. Methods: Combined mouse models of diet‐induced obesity (DIO) and ligation‐induced periodontitis (5‐ or 10‐day ligation) were studied. Fasting serum glucose (FSG), fasting insulin (Fins), and lipids including triglyceride (TG), total cholesterol (TC), and low‐ and high‐density lipoprotein cholesterol (HDLC), were detected via biochemistry and enzyme‐linked immunosorbent assay. POWL and homeostasis model assessment of insulin resistance (HOMA‐IR) were calculated. Analysis of covariance was performed to identify confounding effects of POWL. Results: The obesity, periodontitis, and 10‐day groups exhibited greater POWL than corresponding controls ( P <0.01). Without considering POWL, conflicting results were found, including: 1) contradictory changes in HDLC caused by obesity or periodontitis; and 2) unequal levels of FSG, TC, and HDLC between days 5 and 10 in the sham‐ligation controls. Moreover, upregulating effects of periodontitis were found only on TG in the DIO mice, whereas those on Fins, HOMA‐IR, and HDLC were statistically veiled. After the confounding effects of POWL were filtered, periodontitis promoted increased levels of not only TG but also Fins, HOMA‐IR, and HDLC in the DIO mice ( P <0.05). Conclusions: When analyzing the interrelationship between obesity and periodontitis, the confounding effects of an imbalanced POWL should be considered. Otherwise, impact of periodontitis on metabolic dysregulation in obese animals may be underestimated.